Dumbbell power clean, front squat, and power jerk - Hedrick, A. (Strength and Conditioning Journal, 2015)
Power development is an important training goal for many athletes, and the weightlifting movements are effective at developing this quality. However, muscular endurance is also an important physiological adaptation for many athletes. This article describes how the weightlifting movements, and their associated training exercises, when performed in combination, can have a positive effect on muscular endurance.